Impact of psychosocial stress on facial emotion recognition in schizophrenia and controls: an experimental study in a forensic sample - Hachtel, Henning; Deuring, Gunnar; Graf, Marc; Vogel, Tobias (Frontiers in Psychiatry, 2024)
Given the outstanding contribution of Frontiers in Psychiatry and its Forensic section in the field of diagnostics and evaluation of forensic patients in regard to schizophrenia in the past, the author team wanted to submit our original research in your journal. The manuscript is an experimental study to compare the subjective and neuroendocrine responses due to psychosocial stress of individuals with chronic forms of schizophrenia (PAT) to a healthy control group, its impact on facial emotion recognition(FER) and performance in an arithmetic task. Current literature lacks data on the impact of psychosocial stress on FER in PAT samples and samples in forensic settings. The study focuses also on subjective experienced strain and cortisol levels while controlling for known predictors of cognitive performance like childhood trauma, substance use, parental bonding and intelligence. The results highlight the importance of psychosocial components of therapy interventions to strengthen stress resilience and impart awareness for impaired affect recognition in schizophrenia.